Integrating Multiple Intelligences in Problem-Solving Approaches to Enhance Fiqh Learning for Middle School Students - Musonif, Irfan; Mahin Anas Romadona; Minan Ainur Fatah; Muhammad Fakhriz Zaman; Azis, Donny Khoirul; Nasrin, Samina (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the implementation of multiple intelligences (MI)-based problem-solving strategies in Fiqh learning for Grade VII students at MTs Ma’arif Rakit Banjarnegara. The research responds to a persistent epistemological gap in Islamic pedagogy, where conventional Fiqh instruction emphasizes textual memorization and deductive reasoning at the expense of student engagement and critical reflection. Such practices constrain students’ capacity to relate Islamic jurisprudence to contemporary moral and social realities. Adopting a qualitative descriptive design informed by an interpretivist approach, data were collected through interviews, classroom observations, and document analysis. The findings reveal that MI-based problem-solving transforms learning processes by positioning students as active interpreters of religious meaning. Learning unfolded through four interrelated stages problem identification, argument analysis, practical application, and reflective evaluation each aligned with distinct domains of intelligence such as linguistic, logical, kinesthetic, and interpersonal. Thematic coding and triangulated validation indicated consistent patterns of increased participation, dialogical reasoning, and spiritual self-awareness across learning contexts. Analytically, the study advances an interpretive model of constructivist Islamic pedagogy, demonstrating how the integration of MI and problem-solving can reconfigure epistemic practices in Fiqh learning. This model contributes new insight into how differentiated intelligence frameworks can operationalize reflective, value-oriented learning consistent with the transformative aims of the Merdeka Curriculum.